Case report: Variability in clinical manifestations within a family with incontinentia pigmenti - Belysheva, Tatiana; Nasedkina, Tatiana; Kletskaya, Irina; Volchek, Dana; Barinova, Irina; Semenova, Vera; Gadzhigoroeva, Aida; Zelenova, Ekaterina; Valiev, Timur; Sharapova, Elena; Michenko, Anna; Allenova, Anastasiia; et al. (Frontiers in Medicine, 2024)
Diagnosing skin diseases in children can be a complex interdisciplinary problem. Incontinentia pigmenti (IP), also known as Bloch-Sulzberger syndrome, is a rare hereditary genodermatosis related to a mutation in the IKBKG gene. We present a family case of IP described from the perspective of various specialists, including dermatologists, oncologists, geneticists, dentists, and trichologists. The peculiarity of this case is the development of squamous cell carcinoma (SCC) on the shin of a 10-year-old female patient with IP. The patient had a positive family history: her mother and two sisters also displayed clinical manifestations of IP with involvement of skin, teeth and hair. The presence of exons 4–10 deletion in the IKBKG gene in all affected females was confirmed by detailed genetic evaluation using long-range PCR, and also high degree of X-chromosome inactivation skewing was demonstrated. The family underwent a comprehensive examination and was followed up for 2 years with successful symptomatic treatment of dermatologic manifestations. Recommendations were also made regarding dental and hair problems. By the end of the follow-up period, patients had stabilized, with the exception of a 36-year-old mother who developed generalized morphea. The study demonstrates the varying expressiveness of clinical symptoms among family members and emphasizes the importance of timely diagnosis for effective management of patients with IP.